17 a²b + 15ab²- 11ab² + 13 a²b - ab

8a + 17ab + 2b² + 13ba - bb + a² - 3 × 10ab - b² - aa - 2a × 4

0,3 ab - a² + 2ab - 0,7 a² + a² + ab

5/8 k² - 7/3 kl + 1/4 k² - 3/2 k² - 5/6 kl

Zredukuj wyrazy podobno ,
chodzi mi o wszystkie obliczenia , nie sam wynik

1

Odpowiedzi

Najlepsza Odpowiedź!
2010-01-06T16:11:41+01:00
17 a²b + 15ab²- 11ab² + 13 a²b - ab = 30a²b+4ab²-ab

8a + 17ab + 2b² + 13ba - bb + a² - 3 × 10ab - b² - aa - 2a × 4 = -b²

0,3 ab - a² + 2ab - 0,7 a² + a² + ab = 3,3ab-0,7a²

5/8 k² - 7/3 kl + 1/4 k² - 3/2 k² - 5/6 kl = 2 3/8k²-3 1/6kl